Kesantunan Berbahasa dalam Whatsapp di Lingkungan Rukun Tetangga - Sri Puji Astuti (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
The purpose of this study is to reveal the politeness maxim of what is obeyed and the maxim of what is violated in the Whatsapp group of PKK RT 04 RW XXIII Kelurahan Meteseh, Kecamatan Tembalang, Semarang. This research data is a piece of discourse taken from the group Whatsapp messages by choosing the topic of commemorating the 74th Anniversary of the Independence of the Republic of Indonesia. Once the data is collected, it is then analyzed by using linguistic politeness theory. Based on the results of the study, communication via Whatsapp of the PKK group complied with six maxims. Obedience to these six maxims causes a more harmonious relationship between group members. In addition to obeying the sixth maxim, this Whatsapp group also violates the maxim of wisdom and the maxim of sympathy that was aimed at humor.